PENENTU SEKTOR UNGGULAN DALAM PEMBANGUNAN DAERAH: Studi Kasus di Kabupaten Ogan Komering Ilir - Basuki, Agus Tri; Gayatri, Utari (Jurnal Ekonomi & Studi Pembangunan, 2009)
This study aims to identify the dominant sector in Komering Ogan Ilir. By using the analytical approach of MRP, Shift Share, LQ, Overlay and Klassen typology can be concluded that the economic potential held Komering Ogan Ilir is the agricultural sector and the manufacturing industry which is the dominant sector growth. In addition, the sector also showed an increase of the structure of economic growth. It is given that most residents in thearea of OKI regency is still engaged in agriculture, so agriculture has an outstanding growth of other sectors. In addition, the manufacturing industry has also an outstanding growth among manufacturing Kemplang and Pempek industries that thriving in South Sumatra Province and District OKI.